The Smell of Death: An Unusual Case of Poisoning With the Organophosphorus Pesticide Chlorfenvinphos. Issue 2 (April 2019) - Couchman, Lewis; Slaughter, John A.; Coombes, Gemma; Johnston, Atholl; Ogoti, Evans; Holt, David W.
Abstract : Supplemental Digital Content is Available in the Text.